2017
DOI: 10.1016/j.physleta.2017.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Generating three-qubit quantum circuits with neural networks

Abstract: A new method for compiling quantum algorithms is proposed and tested for a three qubit system. The proposed method is to decompose a a unitary matrix U, into a product of simpler U j via a neural network. These U j can then be decomposed into product of known quantum gates. Key to the effectiveness of this approach is the restriction of the set of training data generated to paths which approximate minimal normal subRiemannian geodesics, as this removes unnecessary redundancy and ensures the products are unique… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(70 citation statements)
references
References 15 publications
1
60
0
Order By: Relevance
“…These are parametric non-linear models which play a prominent role in many machine learning tasks, such as dimensionality reduction, classification, and feature extraction [50,51]. NNs have also recently proven useful for several problems in quantum many-body theory [52][53][54][55][56][57][58][59], quantum compilation [60], quantum stabilizer codes [61] and entanglement quantification [62].…”
Section: Appendix B Supervised Learning Approachmentioning
confidence: 99%
“…These are parametric non-linear models which play a prominent role in many machine learning tasks, such as dimensionality reduction, classification, and feature extraction [50,51]. NNs have also recently proven useful for several problems in quantum many-body theory [52][53][54][55][56][57][58][59], quantum compilation [60], quantum stabilizer codes [61] and entanglement quantification [62].…”
Section: Appendix B Supervised Learning Approachmentioning
confidence: 99%
“…Machine learning techniques involving neural networks were also used to study quantum and fault-tolerant error correction (Baireuther et al , 2017; Breuckmann and Ni, 2017; Chamberland and Ronagh, 2018; Davaasuren et al , 2018; Krastanov and Jiang, 2017; Maskara et al , 2018), estimate rates of coherent and incoherent quantum processes (Greplova et al , 2017), to obtain spectra of 1 /f -noise in spin-qubit devices (Zhang and Wang, 2018), and the recognition of state and charge configurations and auto-tuning in quantum dots (Kalantre et al , 2017). In quantum information theory, it has been shown that one can perform gate decompositions with the help of neural nets (Swaddle et al , 2017). In lattice quantum chromodynamics, DNNs have been used to learn action parameters in regions of parameter space where principal component analysis fails (Shanahan et al , 2018).…”
Section: An Introduction To Feed-forward Deep Neural Network (Dnns)mentioning
confidence: 99%
“…It may not be obvious how to optimize algorithms for a given connectivity and a given gate set. This motivates the idea of an automated approach for discovering and optimizing quantum algorithms [6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%